Cohesion and Coherence in Grade 9 Punjab English Textbook: A Systemic Functional Grammar Analysis - Parveen, Mehwish; Fatima, Sana; Qasim, Hafiz Muhammad (Annals of Human and Social Sciences, 2025)
This work evaluates the structure and coherence in the Grade 9 Punjab English textbook using Halliday and Hasan’s (1976) model, focusing on its usefulness in developing writing skills among ESL learners. This study is designed on Systemic Functional Grammar (SFL), analyzing cohesion in the texts of the Textbook to highlight the need for cohesive devices to enhance learners’ competence in discourse. A qualitative descriptive approach was used to analyze the texts, which were manually annotated using the UAM Corpus Tool, examining cohesion using reference, conjunction, ellipsis, substitution, and lexical devices. Cohesion mainly relied on personal references and collocations, with no use of substitution or ellipsis. The textbook aids clarity but lacks complex cohesive devices. To address these limitations, the textbook should incorporate cohesive devices and include exercises for comprehensive discourse skill development.